Analisis Stilistika Pada Lirik Lagu Album Jumping Car Oleh HEY! SAY! JUMP - Ayu Rini Khoirunnisa; Idah Hamidah; Hartati Hartati (Program Studi Sastra Jepang, Universitas Jenderal Soedirman, 2020)
This research examines the style of language in song lyric entitled “A Stylistic Analysis of Hey! Say! Jump’s Song Lyrics in Jumping Car Album”. This research aims to find out the kinds of language style and describe the meaning of the song lyrics. Language style theory used in this research is theory proposed by Keraf. This research used a descriptive research with qualitative approach. The data collection technique employed in this research was listening and note taking technique. Collected data were analyzed by using equivalent technique and technique of immediate constituent analyst. Data source used in this research is twelve song lyrics in Jumping Car album. The kinds of language style found consists of 3 (three) metaphor, 5 (five) personification, 7 (seven) simile, 16 (sixteen) allegory, 1 (one) eponym, 1 (one) synecdoche, 4 (four) metonymy, 1 (one) epithet, 1 (one) antonomasia, 1 (one) cynicism and 1 (one) sarcasm. The dominant kinds of language in this research is allegory. All of the meaning of the kinds of language which found shows songs in Jumping Car album describing love and life story in which contain happiness and sadness.